Altered motivation masks appetitive learning potential of obese mice - Harb, Mazen R.; Almeida, Osborne F. X. (Frontiers in Behavioral Neuroscience, 2014)
Eating depends strongly on learning processes which, in turn, depend on motivation. Conditioned learning, where individuals associate environmental cues with receipt of a reward, forms an important part of hedonic mechanisms; the latter contribute to the development of human overweight and obesity by driving excessive eating in what may become a vicious cycle. Although mice are commonly used to explore the regulation of human appetite, it is not known whether their conditioned learning of food rewards varies as a function of body mass. To address this, groups of adult male mice of differing body weights were tested two appetitive conditioning paradigms (pavlovian and operant) as well as in food retrieval and hedonic preference tests in an attempt to dissect the respective roles of learning/motivation and energy state in the regulation of feeding behavior. We found that i) the rate of pavlovian conditioning to an appetitive reward develops as an inverse function of body weight; ii) higher body weight associates with increased latency to collect food reward; and iii) mice with lower body weights are more motivated to work for a food reward, as compared to animals with higher body weights. Interestingly, as compared to controls, overweight and obese mice consumed smaller amounts of palatable foods (isocaloric milk or sucrose, in either the presence or absence of their respective maintenance diets: standard, low fat-high carbohydrate or high fat-high carbohydrate). Notably, however, all groups adjusted their consumption of the different food types, such that their body weight-corrected daily intake of calories remained constant. Thus, overeating in mice does not reflect a reward deficiency syndrome and, in contrast to humans, mice regulate their caloric intake according to metabolic status rather than to the hedonic properties of a particular food. Together, these observations demonstrate that excess weight masks the capacity for appetitive learning in the mouse.